2008
DOI: 10.1002/marc.200800456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MgCl2 Crystallographic Structure on Active Centre Formation in Immobilized Single‐Centre and Ziegler–Natta Catalysts for Ethylene Polymerization

Abstract: The ability of a MgCl2 support to activate a transition metal catalyst has been found to depend both on the crystallographic structure of the support and on the nature of the catalyst. A high degree of crystallographic disorder can be very effective for the immobilization and activation of titanium and vanadium complexes, but is not necessarily effective for zirconocene activation. A highly disordered support prepared by the reaction of MgBu2 with HCl gave high activity with TiCl4 but low activity with (n‐PrCp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 27 publications
5
28
0
Order By: Relevance
“…The results shown that higher residual ethanol in particles gave lower crystallographic disorder. In the other hand, lower residual ethanol gave higher crystallographic disorder which consistent with this research [16]. …”
Section: Residual Alcohol In Mgcl2 Particlessupporting
confidence: 90%
“…The results shown that higher residual ethanol in particles gave lower crystallographic disorder. In the other hand, lower residual ethanol gave higher crystallographic disorder which consistent with this research [16]. …”
Section: Residual Alcohol In Mgcl2 Particlessupporting
confidence: 90%
“…A very active catalyst for ethylene polymerization was for example obtained by immobilization of (n-PrCp) 2 ZrCl 2 on magnesium support of type MgCl 2 Á1.1EtOH/AlEt 3 . 19 Its activity results from the presence of the support sites with high Lewis acidity. A similar type of the magnesium support, i.e., MgCl 2 Án(alcohol) (for C 2 H 5 OH n ¼ 3.33 and for CH 3 OH n ¼ 4) modified with an organoaluminium compound (triisobutylaluminium being the best in that group) was also used to immobilize other metallocenes, Cp 2 ZrCl 2 and rac-Et[Ind] 2 ZrCl 2 , which were then utilized in ethylene copolymerization with 1-hexene.…”
Section: Introductionmentioning
confidence: 99%
“…This is because α-MgCl2 turned into the active -MgCl2 resulting in the disappearance of peak at 2θ = 14.4°, 29.7°, 34.3°and 49.5°. This indicated that the -MgCl2 support has a single Cl-Mg-Cl structural layers (monolayers) [22]. Therefore, the modification of α-MgCl2 form into active δ-MgCl2 form led to the increase in the interplanar distance or decrease in 2θ value [23].…”
Section: Xrd Measurement Of Catalystsmentioning
confidence: 97%
“…While three peaks at 2θ = 29.7°, 34.3° and 49.5° were found and assigned to be the stacking faults of the triple layers. The peaks at 2θ = 34.3° and 49.5° represented the (104) and (110) plane, respectively [21,22]. Cat-A and Cat-B exhibited the reduction of intensity in all peaks of α-MgCl2.…”
Section: Xrd Measurement Of Catalystsmentioning
confidence: 99%